THE RELATIONSHIP OF WORK ATTITUDE AND DURATION OF RIDING WITH LOW BACK PAIN (LBP) IN ONLINE OJEK MOTORCYCLE DRIVERS IN PEKANBARU CITY - putri, retno; Sari, Indah Permata; Delidios, Delidios; Ruswaldi, Ruswaldi (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Low back pain (LBP) is a pain that occurs around the lower back (lumbosacral), in the form of local pain or radicular pain, which is acute or chronic which becomes a health problem. Low back pain is a complaint that is often experienced by most of the world's population and is also a common cause of disability and decreased work activities. The World Health Organization (WHO) reports that in developed countries, approximately 70-80% of the population has experienced low back pain, 55-45% of adults experience low back pain every year. In industrialized countries, approximately 80% of the population has experienced low back pain. Several risk factors related to low back pain, namely individual factors and work factors, work consisting of workload, work duration, work attitude. Unnatural work attitude is a work attitude with the position of the body part away from the anatomical position of the body. Back too bent, head raised, hand movements raised. The wrong sitting posture can cause low back pain when done repeatedly. An initial survey conducted using the Nordic Body Map (NBM) on August 20, 2021, which was conducted on 20 online motorcycle taxi driver who were met randomly, 16 people (80%) out of 20 online motorcycle taxi drivers experienced Low Back Pain. and 4 people (20%) felt other complaints, namely neck, shoulder, head and wrist pain. An analytical observational study with a cross sectional approach. The sampling technique is accidental sampling by using the Spearman rank correlation test. There is a relationship between work attitude (pvalue = 0.000) and driving duration (p-value = 0.000) with complaints of Low back pain on online motorcycle taxi riders in the city of Pekanbaru